Catalysis and Stability Effect of Solvent Alcohol on the C6 Aldose Conversion toward Tetrose. Issue 16 (18th March 2019) - Hou, Wenrong; Yan, Yueer; Li, Gang; Zhan, Yulu; Feng, Lei; Zhang, Ruohong; Hua Li, Zhen; Zhang, Yahong; Tang, Yi
Abstract: Conversions of biomass feedstock into various valuable chemicals are of great significance. As a typical route, retro‐aldol condensation of monosaccharide greatly expands the variety of biomass‐derived platform chemicals via a selective C−C splitting. Herein, we describe a solvent‐catalysed strategy to high‐selectively accumulate tetrose (four‐carbon platform chemical) from C6 aldoses via the retro‐aldol/aldol process. We find that alcohol solvents with Lewis acidity facilitate the C−C splitting process of hexose under the catalyst‐free condition. The conversion is the fastest in methanol while it is the slowest in isopropanol. The product distribution is greatly influenced by the alcohols through shifting the equilibrium between tetrose and glycolaldehyde (GA). The addition of catalyst only accelerates the reaction rate, and does not change the product distribution. On the one hand, the acetalization of GA with methanol or ethanol shifts the equilibrium from tetrose toward GA, which results in a low yield of tetrose in methanol or ethanol solvent. On the other hand, tetrose can be well accumulated in isopropanol or n‐butanol, and the yield of tetrose in isopropanol is higher than in n‐butanol because tetrose can be well solvated and stabilized in it. This solvent‐dependent reaction strategy provides a new possibility which contributes to the conversion of biomass feedback into valuable platform chemicals and accumulation of target products by utilizing the solvation effect. Abstract : Unconventional catalysis : a strategy was proposed to accumulate tetrose from C6 aldoses where the Lewis acidic alcohol solvent acts as catalyst. Tetrose can be effectively accumulated due to the stabilization effect of the alcohol solvent.